The role of endothelial frequency in the cerebral blood flow control during neonatal asphyxia: a retrospective longitudinal study - Sergio Agudelo-Pérez; Gloria Troncoso; Cristian Muños Diaz; Juan David Botero-Machado; Daniel Alfonso Botero-Rosas; Eduardo Tuta-Quintero (BMC, 2024)
Abstract Background Cerebral blood flow dynamics can be explored through analysis of endothelial frequencies. Our hypothesis posits a disparity in endothelial activity among neonates with perinatal asphyxia, stratified by the presence or absence of neuronal lesions. Methods We conducted a retrospective longitudinal study involving newborns treated with hypothermia for moderate to severe asphyxia. Participants were grouped based on the presence or absence of neuronal damage to investigate temporal endothelial involvement in cerebral blood flow regulation. Regional cerebral oxygen saturation (rScO2) was measured using near-infrared spectroscopy (NIRS), and temporal series were analyzed in the frequency domain, utilizing the original frequency of the INVOS™ device. Results The study included 88 patients, with 53% (47/88) being male and 33% (29/88) demonstrating brain lesions on magnetic resonance imaging. Among them, 86% (76/88) had a gestational age exceeding 37 weeks according to the Ballard scale, and 81% (71/88) had a birth weight exceeding 2500 g. Cohen's d effect size was calculated to assess differences in endothelial frequency between groups, indicating a small effect size based on cerebral MRI findings (Cohen's d values for Day 2 = 0.2351 and Day 3 = 0.2325). Conclusion NIRS represents a valuable tool for monitoring cerebral autoregulation in neonates affected by perinatal asphyxia, underscoring the utility of assessing endothelial frequency or energy on rScO2 measured by NIRS using the original INVOS™ device frequency.